PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) BERBANTUAN MEDIA PAPAN NILAI TEMPAT UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PADA MATERI NILAI TEMPAT SISWA KELAS II SDN BULANG 1 - Rahmaudina Rizkiyah; Ribut Prastiwi Sriwijayanti; Lia Ardiansari (STKIP Subang, 2026)
ABSTRACT This study was conducted to improve the mathematics learning outcomes of second-grade students on the topic of place value through the implementation of the Problem-Based Learning (PBL) model assisted by place value board media at SDN Bulang 1. The research was motivated by the low student achievement caused by teacher-centered instructional practices and the limited use of interactive learning media, resulting in many students failing to meet the minimum mastery criteria. This research employed Classroom Action Research (CAR) consisting of two cycles, with each cycle comprising planning, implementation, observation, and reflection stages. The participants were 16 second-grade students. Data were collected through observation and learning outcome tests and analyzed descriptively to evaluate improvements across the cycles. The findings demonstrated that the application of the Problem-Based Learning model supported by place value board media effectively enhanced students’ mathematics learning outcomes. In the pre-test, only 5 students (31.25%) achieved mastery, while 11 students (68.75%) did not. After the implementation of Cycle I, the number of students achieving mastery increased to 10 (62.5%). Further improvement was observed in Cycle II, where 15 students (93.75%) met the mastery criteria and only 1 student (6.25%) remained below the expected standard. These results indicate that integrating the Problem-Based Learning model with place value board media creates a more active and meaningful learning environment and significantly improves students’ understanding and achievement in learning place value concepts. Keywords: Problem Based Learning, Scoreboard, Learning Outcomes